Fatigue testing of thin CoNiCr wire up to 1010 cycles. (May 2017) - Fitzka, Michael; Catoor, Dhiraj; Irrasch, Daniel; Reiterer, Markus; Mayer, Herwig
Highlights: Ultrasonic fatigue testing has been adapted to thin wires. Fatigue properties of 100 μm diameter wire have been investigated in the VHCF regime. Good agreement with conventional fatigue tests was found. No fatigue limit was found up to more than 10 10 cycles. Crack initiation in as-drawn low-Ti MP35N wire occurs exclusively at the surface. Abstract: The CoNiCr alloy MP35N in the form of thin wires is commonly used as conductor in cardiac leads. The application requires high fatigue strength, in particular in the very high cycle fatigue (VHCF) regime. High frequency fatigue testing techniques are of great interest for material characterization and development since existing techniques require very long testing times. In this study, adapting the ultrasonic fatigue testing method to sub-millimeter wires has been accomplished for the first time. Fatigue tests of as-drawn low-Ti MP35N wire with 100 μm diameter have been performed with a novel technique at 20 kHz cycling frequency at load ratio R  = 0.3. Measured lifetimes show good agreement with conventional servo-hydraulic tension-tension fatigue data of the same material at 30 Hz. Ultrasonic tests were run up to 2 × 10 10  cycles, and no fatigue limit was observed. Crack initiation occurs at Al2 O3 -inclusions at the surface, where the interfaces between particles and matrix fail. Sizes of the crack initiating inclusions, area inc . are between 1.9 μm and 3.5 μm. Fatigue lifetimes can be approximated with a single S-N curve between 10 4 and 10 10 cycles. No change of crack-initiation mode into the interior is observed when lifetimes extend into the VHCF regime. Inclusions can be considered as initial cracks, and a fracture mechanics concept is used to describe fatigue lifetimes. On average a stress intensity range as low as 1.0 MPa m can propagate the crack to fracture at lifetimes above 10 8  cycles.